Molecular Imaging of Gliomas - A. H. Jacobs; C. Dittmar; A. Winkeler; G. Garlip; W. D. Heiss (Molecular Imaging)
Gliomas are the most common types of brain tumors. Although sophisticated regimens of conventional therapies are being carried out to treat patients with gliomas, the disease invariably leads to death over months or years. Before new and potentially more effective treatment strategies, such as gene- and cell-based therapies, can be effectively implemented in the clinical application, certain prerequisites have to be established. First of all, the exact localization, extent, and metabolic activity of the glioma must be determined to identify the biologically active target tissue for a biological treatment regimen; this is usually performed by imaging the expression of up-regulated endogenous genes coding for glucose or amino acid transporters and cellular hexokinase and thymidine kinase genes, respectively. Second, neuronal function and functional changes within the surrounding brain tissue have to be assessed in order to save this tissue from therapy-induced damage. Third, pathognomonic genetic changes leading to disease have to be explored on the molecular level to serve as specific targets for patient-tailored therapies. Last, a concerted noninvasive analysis of both endogenous and exogenous gene expression in animal models as well as the clinical setting is desirable to effectively translate new treatment strategies from experimental into clinical application. All of these issues can be addressed by multimodal radionuclide and magnetic resonance imaging techniques and fall into the exciting and fast growing field of molecular and functional imaging. Noninvasive imaging of endogenous gene expression by means of positron emission tomography (PET) may reveal insight into the molecular basis of pathogenesis and metabolic activity of the glioma and the extent of treatment response. When exogenous genes are introduced to serve for a therapeutic function, PET imaging may reveal the assessment of the “location,” “magnitude,” and “duration” of therapeutic gene expression and its relation to the therapeutic effect. Detailed reviews on molecular imaging have been published from the perspective of radionuclide imaging (Gambhir et al., 2000; Blasberg and Tjuvajev, 2002) as well as magnetic resonance and optical imaging (Weissleder, 2002). The present review focuses on molecular imaging of gliomas with special reference on the status and perspectives of imaging of endogenous and exogenously introduced gene expression in order to develop improved diagnostics and more effective treatment strategies of gliomas and, in that, to eventually improve the grim prognosis of this devastating disease.